Pete the cat: Five little pumpkins - Dean, James 1957- (Harper / HarperCollins, 2015)
Pete the Cat takes on the classic favorite children's song "Five Little Pumpkins" in New York Times bestselling author James Dean's Pete the Cat: Five Little Pumpkins. Join Pete as he rocks out to this cool adaptation of the classic Halloween song!
Keywords: Cats / Juvenile fiction; Jack-o-lanterns / Juvenile fiction; Halloween / Juvenile fiction; Children's songs / Adaptations